ABOUT THE SECODARY LIAPUNOV’S METHOD FOR DIFFERENTIAL EQATIONS WITH IMPULSES - Гургула, Степан Іванович; Собкович, Роман Іванович; Перкатюк, Ігор Йосипович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Criteries of stability, asymptotic stability and non-stability of simple solution in an analogy to those according to the secondary Liapunov’s method for differential equations without impulses, were issued for autonomial system of ordinary differential equations with impulsive action in the fixed moments of time.